Gambaran Budaya Kerja Organisasi Terhadap Adaptasi Rekam Medis Elektronik dalam Pelayanan Kesehatan di Rumah Sakit - Sabran Sabran; Maya Weka Santi; Dony Setiawan Hendyca Putra; Mochammad Choirur Roziqin (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Electronic Medical Records (EMR) have become a vital system aimed at enhancing the efficiency of patient data management in hospitals. EMR is not just an innovation but a necessity that all healthcare services in Indonesia must adhere to, aligning with the targets set forth in the National Medium-Term Development Plan (RPJMN). In this context, several supportive factors play a pivotal role in EMR implementation, including organizational work culture, human resources, infrastructure, governance, and leadership. This research aimed to provide insight into hospital preparedness in the context of organizational work culture to ensure the smoother implementation of EMR. The research employed a quantitative approach with descriptive analysis. The research subjects were medical record personnel working in hospitals, with data collected from 15 hospitals of various types in the East Java region. The results of this study highlight several critical aspects of organizational work culture that influence EMR implementation, including training, socialization, mentoring, commitment, support from medical record personnel, and an understanding of how technology can enhance service quality. Nevertheless, the research also identified a prevailing perception that EMR is merely an Information Technology project, which could act as a potential hindrance to successful implementation. This research served as a reminder to hospitals about the importance of paying attention to these aspects as part of comprehensive preparations for EMR implementation. Consequently, it is anticipated that EMR implementation can proceed more efficiently and effectively, delivering greater benefits to patients and overall healthcare service delivery.